Penerapan Program Sepuluh Langkah Kesehatan untuk Peningkatan Pemberian ASI Eksklusif: Model Evaluasi CIPP (Context, Input, Process, Product) - Novianti Indah Fatmawati; Thinni Nurul Rochmah; Anis Wulandari; Andini Yulina Pramono (Universitas Aisyah Pringsewu, 2021)
This study aimed to evaluate the ten steps to successful breastfeeding policy implementation as the basis to enhance the achievement of exclusive breastfeeding practices in the Kediri District. This study was an evaluative study using the CIPP (Context, Input, Process, Product) model. There were seven inpatient primary healthcare centres involved in this study. Respondents in this study were the head and staff of primary healthcare centres and all midwives. The results show that based on the context evaluation, the objective of the policy implementation reached 77.6%. The input evaluation showed that the infrastructure and facilities, as well as the health personnel’ support, was not adequate with a value of 56.4%. In terms of the process evaluation, the primary healthcare centres have not carried out formulating the policy and forming supporting groups for breastfeeding with a score of 73.9%. In the product evaluation, exclusive breastfeeding decreased in 2018 and stay behind the trend in the past four years. It has not met the target of a strategic plan formulated by the regional government. In conclusion, the policy of ten steps to successful breastfeeding in the inpatient primary healthcare centres has not been implemented well. It is recommended that the local government should formulate regulations about exclusive breastfeeding. The District Health Office should socialize the ten steps to successful breastfeeding and include it in the assessed elements in the accreditation of primary healthcare centres. Moreover, the District Health Office should guide and give rewards to health facilities, as well as a guide to the health-related organization by cooperating with baby milk producers and improve the knowledge and skills of health personnel about breastfeeding counselling. Abstrak: Penelitian ini bertujuan untuk mengevaluasi sepuluh langkah keberhasilan implementasi kebijakan ASI sebagai dasar untuk meningkatkan pencapaian praktik ASI eksklusif di Kabupaten Kediri. Penelitian ini merupakan penelitian evaluatif dengan model CIPP (Context, Input, Process, Product). Ada tujuh Puskesmas rawat inap yang terlibat dalam penelitian ini. Responden dalam penelitian ini adalah kepala atau staf puskesmas (7 orang) dan seluruh bidan (94 orang). Hasil penelitian menunjukkan bahwa berdasarkan evaluasi konteks, berupa tujuan pelaksanaan kebijakan tercapai 77,6%. Evaluasi masukan menunjukkan bahwa sarana dan prasarana serta dukungan tenaga kesehatan kurang memadai, hanya tercapai 56,4%. Berdasarkan hasil evaluasi proses, Puskesmas belum melakukan perumusan kebijakan dan pembentukan kelompok pendukung ASI, sehingga capaiannya hanya 73,9%. Evaluasi produk, pemberian ASI eksklusif menurun pada tahun 2018 dan tertinggal dari tren selama empat tahun terakhir. Target rencana strategis yang disusun oleh pemerintah daerah belum terpenuhi. Kesimpulan: kebijakan sepuluh langkah keberhasilan menyusui di Puskesmas rawat inap belum terlaksana dengan baik. Disarankan agar pemerintah daerah menyusun regulasi tentang ASI eksklusif. Dinas Kesehatan Kabupaten hendaknya mensosialisasikan kesepuluh langkah sukses menyusui dan memasukkannya ke dalam elemen penilaian dalam akreditasi Puskesmas. Selain itu, dibutuhkan pembentukan kelompok KP-ASI di masyarakat.